Reportage : Methodology of Literary Journalism (2018)
ABSTRACT: I sustain in my book El reportaje como metodologia del periodismo: una polifonia de saberes (Reportage as the methodology of journalism: polyphony of knowledge), (Osorio, 2017), that journalism leads, guides, interprets, explains, teaches and above all tries deeply to understand the world and its running; thus its essence is freedom of thought, expression and social dialogue or conversation to set in place and to enhance consensus and democratic participation. In this process, journalism shows and enlightens ways (methods) through reportage, which has been very much so studied as a journalist genre around the world; countless books and articles have been published about it and several universities have granted PhD titles for theses written about it. The North American and European bibliography on it is abundant - which has been taken in consideration at this research - and widely known; but little is known of what has been done in our continent. Therefore, in this book I put in perspective two major examples: Brazil and Colombia. Nevertheless, I must emphasize that when this subject is addressed, it is done so through the lens of journalistic genres, but not under the dimension of the methodology of journalism, which has been away from the eyes of theoreticians, scholars and researchers. In this sense, my book is an epistemological turn, as it is innovative and pioneer for contributing with another vision, which studies, analyses and proposes reportage as the methodology of journalism, by presenting some findings and by opening new theoretical perspectives in literary journalism.